Exploring the Determinants of Repurchase Intentions for Users of Goods Delivery Services - Yunus, Mukhlis; Alexandri, Mohammad Benny; Adam, Muhammad; Ibrahim, Mahdani; Idris, Sofyan (Indatu Journal of Management and Accounting, 2023)
Repurchase intentions are crucial for users of goods delivery services, as they directly influence customer trust and brand loyalty. Regarding this importance, this study aims to determine the influence of service quality, price suitability, and online service facilities on repurchase intentions, with customer satisfaction as an intervening variable for goods delivery service users in Aceh Province, Indonesia. Utilizing a sample of 220 people, the results of the Structural Equation Modeling (SEM) method demonstrate that service quality, price suitability, and online service facilities significantly and positively influence repurchase intentions. Moreover, customer satisfaction is found to mediate the influence of service quality, price suitability, and online service facilities on repurchase intentions for goods delivery service users. This implies that companies should focus on improving these aspects of their services to encourage repeat business. Establishing a strong base of loyal customers through effective repurchase strategies can lead to long-term growth and sustainability for goods delivery service providers.